STRATEGI PENGEMBANGAN BISNIS SIGER ROEMAH BATIK MELALUI PENDEKATAN BUSINESS MODEL CANVAS (BMC) DAN SWOT ANALYSIS - Susanti, Faradila; Siti Suprihatin; Sangidatus Sholiha (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Siger Roemah Batik in Bandar Lampung faces challenges such as limited use of digital platforms, lack of product design variety, and low market visibility. These issues hinder competitiveness and growth amid strong batik industry competition. This study aims to analyze Siger Roemah Batik’s business model and develop strategies using Business Model Canvas (BMC) and SWOT Analysis. The qualitative descriptive method was applied, with data gathered from interviews, observations, and questionnaires. The nine BMC elements were evaluated to identify internal and external factors. Results show that combining BMC and SWOT provides deep insight into the business model and supports innovative strategy formulation. Suggested strategies include product diversification, optimizing distribution channels, strengthening customer relationships, and integrating digital platforms to expand market reach. Applying BMC and SWOT proves effective for sustainable MSME business strategies. For further research, it is recommended to conduct direct observation to measure the effectiveness of the strategy and conduct comparative studies with other batik MSMEs for insight into key success factors and explore product innovation and digital marketing to increase market appeal in the digital era.